Correlações entre vulnerabilidades e soroprevalência de infecções sexualmente transmissíveis em homens privados de liberdade - Carlos Eduardo Prates Fonseca (2024)
Introduction: Studies on inmate health show it’s relevance as a public health matter and call for specific policies targeting people deprived of liberty (PDL) to be carried out. Prisoner health structures are known to possess many fragilities, such as programmatic and non programmatic accessibility barriers and elevated high-risk behavior, which results in increased vulnerability and elevated risk for multiple health deteriorating events such as IST contraction. Objective: To analyze how individual, social and programmatic prison health care vulnerabilities contribute to the STI chain of infection among people deprived of liberty. Methods: this is a transversal descriptive, documental and analytical study, developed using a quantitative and qualitative approach. The Research sample consisted of both incarcerated men from 11 prisons in one of Minas Gerais public security areas and health professionals currently working on the area’s largest detention center. A socio economic questionnaire consisting of structured questions was applied to the PDL, as well as rapid HIV, syphilis and hepatitis types “B” and “C” tests. These results were analyzed through a quantitative approach. Interviews with the healthcare workers, non participant observation and documentary research were conducted within the facility’s Basic Health Unity. Quantitative data was analyzed statistically and qualitative data was processed using IRAMUTEQ software and subsequently analyzed through content analysis. Results: 273 inmates’ data was analyzed. 6,3% of which tested positive for anti-HIV, 87,5% of which had their results later confirmed. 3% tested positive for anti-HCV, 1,1% for HBsAg and 11% for the TB antigen test. Significant association was shown between HIV positivity and precarious housing conditions (Odds Ratio – OR = 3,4 IC95% = 1,3; 9,4). The smaller parcel of PDL who reported having knowledge regarding sexually transmitted diseases (OR – 0,35 IC95% = 0,12; 1,04) and higher income (OR – 0,39 IC95% = 0,16; 0,93) showed lower risk for syphilis infection. 6 healthcare providers took part in the qualitative research, drawing attention to the fact that 95,6% of the interview corpus was applicable, and resulted in 3 categories: professional experiences codependent of security and specialized care service access coordination; Experiences facing the contribution of family and community bonds towards health during prison time; Interdisciplinary actions and professional training: cultural context competences. Conclusion: Most PDL are young, mixed race, single, with inadequate housing conditions prior to imprisonment, have a deficient knowledge on STI transmission mechanisms and considerable social and individual vulnerabilities, largely due to inconsistent use of male condoms among heterosexual individuals and those with a lower level of education. Deep social and individual vulnerabilities are often established in their lives prior to incarceration and tend to exacerbate themselves within the prison. It was recognized among the healthcare workers that, according to the component of programmatic vulnerabilities in the services, there is a need to implement public policies with care protocols, lines of care and special training for health and security professionals in order to manage STIs. There is a necessity for improvements in work processes and multidisciplinary accountability, reducing nursing professionals overload.